farhod THE ROLE AND PLACE OF TRANSLATION IN TEACHING A FOREIGN LANGUAGE: THE ROLE AND PLACE OF TRANSLATION IN TEACHING A FOREIGN LANGUAGE - Norbekov, Farxod (Журнал иностранных языков и лингвистики, 2022)
Translation as a field of knowledge or as a science can be considered as a mysterious job, meaning that looking for equivalents form one language to another is not an easy task.